Karakteristik Taman Menteri Soepeno sebagai Taman Ramah Anak di Kota Semarang - P Prihantini; Wakhidah Kurniawati (Ruang, 2019)
The child-friendly city is a city that gives attention to and recognizes the existence of children's rights, including the provision of children's play facilities. Public facilities that can reflect recognition of children's rights are parks. The purpose of this study is to find out the characteristic of Menteri Soepeno park as a child-friendly park in Semarang city. This park is expected to be a reference for the development of child-friendly parks in realizing a child-friendly city. The method used in this research is quantitative with scoring analysis. The result showed that Menteri Soepeno park was not child-friendly, some improvements were needed so this park could be one of facility that supports the realization of a child-friendly city in Semarang.